From Faith To Action: Forming Islamic Character Through A Sustainable Curriculum At Smait Asy-Syukriyyah - Aris Setyawan; Asriadi Rauf (THORIQOTUNA: Jurnal Pendidikan Islam, 2025)
This study was prompted by the growing crisis of morality and ecological awareness among students, which highlights the urgent need to integrate Islamic values into character education through a sustainable curriculum. The research aims to describe and analyse the implementation of an Islamic-based sustainable curriculum in shaping students’ character at SMAIT Asy-Syukriyyah. Employing a descriptive qualitative approach, data were collected through interviews, observation, and documentation involving teachers, students, parents, and school administrators. The findings reveal that faith, when internalized through a transformative curriculum, becomes a driving force behind students’ concrete actions to protect the environment, making spirituality a core of character formation. The integrated curriculum based on Islamic values successfully bridges cognitive learning and meaningful, sustainable actions